2011
DOI: 10.1007/s11214-011-9810-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric Density: An Overview of Temporal and Spatial Variations

Abstract: Neutral density shows complicated temporal and spatial variations driven by external forcing of the thermosphere/ionosphere system, internal dynamics, and thermosphere and ionosphere coupling. Temporal variations include abrupt changes with a time scale of minutes to hours, diurnal variation, multi-day variation, solar-rotational variation, annual/semiannual variation, solar-cycle variation, and long-term trends with a time scale of decades. Spatial variations include latitudinal and longitudinal variations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
130
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 69 publications
4
130
0
Order By: Relevance
“…These results illustrate that the thermospheric annual asymmetry should be associated with the varying Sun-Earth distance. Actually, previous studies suggested that the difference of solar radiation associated with the difference of Sun-Earth distance between June and December would contribute to the annual asymmetry (Qian et al, 2012;Lei et al, 2013Lei et al, , 2016Emmert, 2015;Calabia et al, 2016). Moreover, Fig.…”
Section: Resultsmentioning
confidence: 91%
“…These results illustrate that the thermospheric annual asymmetry should be associated with the varying Sun-Earth distance. Actually, previous studies suggested that the difference of solar radiation associated with the difference of Sun-Earth distance between June and December would contribute to the annual asymmetry (Qian et al, 2012;Lei et al, 2013Lei et al, , 2016Emmert, 2015;Calabia et al, 2016). Moreover, Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Because T i is closely related to T, a corresponding trend in neutral temperature was estimated to be about dT = À5 K yr À1 , which is substantially greater than predicted by models [e.g., Roble and Dickinson, 1989;Rishbeth and Roble, 1992;Qian et al, 2011;Qian and Solomon, 2012].…”
Section: Introductionmentioning
confidence: 85%
“…[8] Second and perhaps more important, according to model simulations of trends in T, which are in good agreement with independent observational estimates [Beig et al, 2003;Marcos et al, 2005;Akmaev et al, 2006;Qian et al, 2006;Emmert et al, 2008;She et al, 2009;Qian and Solomon, 2012], it appears impossible to quantitatively reconcile them with the estimates of trends in T i regardless of what known cooling mechanisms are invoked. Even though the vertical profiles are qualitatively very similar, with positive and negative trends in the lower and upper thermosphere, respectively, the magnitudes differ tremendously.…”
Section: Introductionmentioning
confidence: 99%
“…Following common conventions, the geomagnetic storm is defined corresponding to 6 6 K p 9 (Montenbruck and Gill, 2000;Rhoden et al, 2000;Qian and Solomon, 2012). The normal level of solar activity corresponds to a typical value of F 10:7 ¼ 155, while a maximum activity corresponding to F 10:7 ¼ 240 (Montenbruck and Gill, 2000).…”
Section: Introductionmentioning
confidence: 99%